2022
DOI: 10.14236/ewic/hci2022.2
|View full text |Cite
|
Sign up to set email alerts
|

Tools and technology to support rich community heritage

Abstract: This paper explores ways in which scholarly skill and expertise might be embodied in tools and sustainable practices that enable communities to create and manage their own digital archives. We focus particularly on tools and practices related to the recording and annotation of digitised materials. The paper is based on co-production practice in two very different kinds of community. Although the communities are different we find that tools designed specifically for one are valuable for others, thus offering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Indeed, it would be transformative if everyday office tools such as word processors and presentation software made it easy to keep references to imported images. In work with humanities and heritage, we have noted how file systems have barely altered since the 1970s (Dix, 2022) -the folder structures allow us to store and roughly classify, but there is virtually no support for talking about documents and about their relationships to one another. Semantic desktop research (Sauermann, 2005), which seemed promising at the time, has never found its way into actual operating systems.…”
Section: Data and Provenancementioning
confidence: 99%
“…Indeed, it would be transformative if everyday office tools such as word processors and presentation software made it easy to keep references to imported images. In work with humanities and heritage, we have noted how file systems have barely altered since the 1970s (Dix, 2022) -the folder structures allow us to store and roughly classify, but there is virtually no support for talking about documents and about their relationships to one another. Semantic desktop research (Sauermann, 2005), which seemed promising at the time, has never found its way into actual operating systems.…”
Section: Data and Provenancementioning
confidence: 99%